Epidural Spinal Cord Stimulation Acutely Modulates Lower Urinary Tract and Bowel Function Following Spinal Cord Injury: A Case Report - Walter, Matthias; Lee, Amanda H. X.; Kavanagh, Alex; Phillips, Aaron A.; Krassioukov, Andrei V. (Frontiers in Physiology, 2018)
Regaining control of autonomic functions such as those of the cardiovascular system, lower urinary tract and bowel, rank among the most important health priorities for individuals living with spinal cord injury (SCI). Recently our research provided evidence that epidural spinal cord stimulation (ESCS) could acutely modulate autonomic circuits responsible for cardiovascular function after SCI. This finding raised the question whether we can modulate autonomic circuits involved in lower urinary tract and bowel control after SCI using ESCS. We present a case of a 32-year-old man with a chronic motor-complete SCI (American Spinal injury Association Impairment Scale B) at the 5th cervical spinal segment. He sustained his injury during a diving accident in 2012. He was suffering from neurogenic lower urinary tract and bowel dysfunction. Epidural stimulation of the lumbosacral spinal cord immediately modulated both functions without negatively affecting the cardiovascular system. Specifically, the individual’s bowel function was assessed using different pre-set configurations and stimulation parameters in a randomized order. Compared to the individual’s conventional bowel management approach, ESCS significantly reduced the time needed for bowel management (p=0.039). Furthermore, depending on electrode configuration and stimulation parameters (i.e. amplitude, frequency and pulse width), ESCS modulated detrusor pressure and external anal sphincter/pelvic floor muscle tone to various degrees during urodynamic investigation. Although, ESCS is currently being explored primarily for restoring ambulation, our data suggest that application of this neuroprosthetic intervention may provide benefit to lower urinary tract and bowel function in individuals with SCI. To fully capitalize on the potential of improving lower urinary tract and bowel function, further research is needed to better understand the neuronal pathways and identify optimal stimulation configurations and parameters.